2021
DOI: 10.1021/acsomega.1c04861
|View full text |Cite
|
Sign up to set email alerts
|

Foam Stabilization Mechanism of a Novel Non-cross-linked Foam Fracturing Fluid

Abstract: Traditional foam hydraulic fracturing fluids used guar crosslinking technology. However, major production problems, such as high friction and difficulty to accurately control the cross-linking time, have influenced the large-scale application of cross-linked guar foam fracturing fluids. In this study, we developed a novel non-cross-linked foam fracturing fluid using a series of polymers synthesized with acrylamide and hexadecyl trimethylallyl ammonium chloride as monomers and improved the stability of foam by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…This supports the assumption that the presence of the polymer increases the foamability of the solution. This occurrence can be a result of slower gas diffusion and liquid drainage from foam bubbles because of higher viscosity . In Figure , only the pressure drop development is shown until it reaches its steady state to avoid various curves crossing each other and making the figure harder to read.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the assumption that the presence of the polymer increases the foamability of the solution. This occurrence can be a result of slower gas diffusion and liquid drainage from foam bubbles because of higher viscosity . In Figure , only the pressure drop development is shown until it reaches its steady state to avoid various curves crossing each other and making the figure harder to read.…”
Section: Resultsmentioning
confidence: 99%
“…This occurrence can be a result of slower gas diffusion and liquid drainage from foam bubbles because of higher viscosity. 61 In Figure 17 , only the pressure drop development is shown until it reaches its steady state to avoid various curves crossing each other and making the figure harder to read. The final equilibrium pressure drop for the outlet section increases slightly as the HPAM concentration increases.…”
Section: Resultsmentioning
confidence: 99%
“…In general, water‐based fracturing fluids such as guar gum and synthetic polymers are the most commonly used types 2–4 . However, guar gum lacks thermal stability and produces significant residue upon breaking which negatively impacts productivity 5,6 . Synthetic polymer‐based fracturing fluids in the oil and gas industry are composed of a polyacrylamide backbone and can be tailored to suit many applications, including clay stabilizers, scale inhibitors, asphaltene dispersants, and wax inhibitors 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] However, guar gum lacks thermal stability and produces significant residue upon breaking which negatively impacts productivity. 5,6 Synthetic polymer-based fracturing fluids in the oil and gas industry are composed of a polyacrylamide backbone and can be tailored to suit many applications, including clay stabilizers, scale inhibitors, asphaltene dispersants, and wax inhibitors. 7,8 Hydrophobic associated polyacrylamides (HAPs) are polymers that contain a few hydrophobic groups or chains (generally <2 mol%) incorporated into a hydrophilic backbone, giving them amphiphilic properties.…”
mentioning
confidence: 99%
“…Yang [10] et al studied the hydrophobic modi ed alumina nanoparticles stabilized foam by using Sodium isopropylbenzene sulfonate (SC) to modify the nanoparticle, which showed that SC concentration could improve the foaming and stability of the foam. Xiong [11] et al…”
Section: Introductionmentioning
confidence: 99%